Changes in calpain activity, protein degradation and microstructure of beef M. semitendinosus by the application of ultrasound. (15th April 2018) - Wang, Anran; Kang, Dacheng; Zhang, Wangang; Zhang, Chaoyang; Zou, Yunhe; Zhou, Guanghong
Highlights: Ultrasound improved the tenderness of beef during postmortem aging; Ultrasound accelerated the activation and autolysis of μ-calpain; Ultrasound resulted in increased degradation of desmin and troponin-T. Abstract: In this investigation, samples were treated by ultrasonic probe (20 kHz) at an intensity of 25 W cm −2 for 20 or 40 min, followed by aging at 4 °C for 1, 3 and 7 d. Ultrasound treatment significantly increased myofibrillar fragmentation index (MFI) and decreased Warner-Bratzler shear force (WBSF) at 3 and 7 d of postmortem aging ( P  < .05). Ultrasound-treated samples showed significantly greater intensities of autolyzed 76 kDa subunits and the lower intensity of intact 80 kDa form compared to control at 1 d of storage ( P <  .05). Significant difference was found between semitendinosus (ST) samples treated for both 20 and 40 min ( P <  .05). Ultrasound treated samples showed increased proteolysis during the postmortem storage as reflected by an increased degradation of desmin and troponin-T. These results showed that ultrasound treatment could improve the tenderness of beef ST muscle through regulating the calpain activation and protein degradation during postmortem aging.